2008
DOI: 10.3892/ijo.32.5.1097
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of long-term mobile phone use and the association with brain tumours

Abstract: Abstract. We evaluated long-term use of mobile phones and the risk for brain tumours in case-control studies published so far on this issue. We identified ten studies on glioma and meta-analysis yielded OR = 0.9, 95% CI = 0.8-1.1. Latency period of ≥10-years gave OR = 1.2, 95% CI = 0.8-1.9 based on six studies, for ipsilateral use (same side as tumour) OR = 2.0, 95% CI = 1.2-3.4 (four studies), but contralateral use did not increase the risk significantly, OR = 1.1, 95% CI = 0.6-2.0. Meta-analysis of nine stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
2
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 36 publications
1
74
2
7
Order By: Relevance
“…The aim of this presentation is not to give a review of this area, since such publications can be found elsewhere (6,7). In addition to our studies only a few publications from the so-called Interphone group give results for 10-year latency (7). That group includes 13 countries and cases and controls were recruited during 1999-2004, varying for different countries.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this presentation is not to give a review of this area, since such publications can be found elsewhere (6,7). In addition to our studies only a few publications from the so-called Interphone group give results for 10-year latency (7). That group includes 13 countries and cases and controls were recruited during 1999-2004, varying for different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it reports selectively chosen data from Hardell's 2006 papers, including his pooled-analyses [1,2] referred to subjects with 5 year latency but does not highlight, for those with 10 year latency, the much more significant data on increases of ipsilateral head tumour risk, although these are clearly indicated in Hardell's papers. Besides, it does not consider the recent studies by Hardell [3,[35][36][37] or those of Interphone [22,24,29,31,32] which report s.s. increases of ipsilateral head tumour risk after 10-year latency or use of cellular phones ( Table 2). Consequently, the Ahlbom metaanalysis gives results that lack any indication of head tumour risk from MP use or latency up to 10 years (Table 3), emphasising the complete incompatibility between the two data sources: 83% of Hardell's risk data (OR) are > 1, of which 43% are s.s., while the Interphone data are largely (73%) < 1, of which 11% are s.s.…”
Section: Resultsmentioning
confidence: 96%
“…In fact, the meta-analyses of Hardell [35,36], Khurana [37], Kundi [38], and ourselves [39], including the literature data on head tumours in people with MP latency or continuous use of at least 10 years -and thus, besides Hardell's data [1][2][3][4]36], also part of the Interphone data [23-25, 29, 31, 32] -show large and s.s. increases (100%) of the risk of ipsilateral gliomas with high level of malignancy, and sizable and s.s. increases (50-140%) of the risk of ipsilateral acoustic neuromas (Table 3). These increases are smaller than those found by Hardell in the pooled analyses of his data alone [1,2,4], being "diluted" with the Interphone data corresponding to the requirements indicated above.…”
Section: Resultsmentioning
confidence: 99%
“…Several meta-analyses of brain tumour studies have been published (e.g. Ahlbom et al, 2009;Hardell et al, 2008;Kan et al, 2008;Lahkola, Tokola & Auvinen, 2006;Myung et al, 2009). Their coverage of studies has varied, affecting the overall results, but most have indicated heterogeneity between study results.…”
Section: Epidemiologymentioning
confidence: 99%